2007
DOI: 10.1089/cpb.2006.9972
|View full text |Cite
|
Sign up to set email alerts
|

Internet Addiction Disorder: An Italian Study

Abstract: The Italian version of the Young's Internet Addiction Test (IAT) was administered online to a sample of Italian chatters (n = 236) who were different in terms of gender, age, and occupation. Results revealed that young users are more at-risk subjects for Internet addiction than adults, perceiving a compromised social and individual quality of their life that led them to make a compensatory usage of the Internet. Similarly, employed users perceive their social and individual quality of life as more compromised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
148
3
23

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(185 citation statements)
references
References 14 publications
11
148
3
23
Order By: Relevance
“…The test has been adopted into different languages and cultures including French (Khazaal et al, 2008), Italian (Ferraro, Caci, D'Amico & Blasi, 2007), Finnish (Korkeila, Kaarlas, Jaaskeleinen, Vahlberg & Taiminen, 2010), Korean (Kim, 2000), Malay (Guan, Isa, Hashim, Pillai & Singh, 2015), and Chinese (Chang & Man Law, 2008) among college students and adults. In the Italian version, six-factor structure (compromised social quality of life, compromised individual quality of life, compensatory usage of the Internet, compromised academic/working careers, compromised time control, and excitatory use) was found.…”
Section: Psychometric Properties Of Iatmentioning
confidence: 99%
“…The test has been adopted into different languages and cultures including French (Khazaal et al, 2008), Italian (Ferraro, Caci, D'Amico & Blasi, 2007), Finnish (Korkeila, Kaarlas, Jaaskeleinen, Vahlberg & Taiminen, 2010), Korean (Kim, 2000), Malay (Guan, Isa, Hashim, Pillai & Singh, 2015), and Chinese (Chang & Man Law, 2008) among college students and adults. In the Italian version, six-factor structure (compromised social quality of life, compromised individual quality of life, compensatory usage of the Internet, compromised academic/working careers, compromised time control, and excitatory use) was found.…”
Section: Psychometric Properties Of Iatmentioning
confidence: 99%
“…The Italian version (Ferraro, Caci, D'Amico, & Di Blasi, 2007) contains twenty Likert-type items using a 5-point scale (from "not at all" to "always"), yielding a maximum score of 100. A sample item is "How often do you find that you stay online longer than you intended?"…”
Section: Measures and Proceduresmentioning
confidence: 99%
“…[5][6][7][8] Adolescence is a period of rapid psychological maturation and of susceptibility to Internet attraction, 9 and adolescents were found to be particularly vulnerable to the negative health impacts of Internet overuse. [10][11][12] Among the negative health impacts, the relationship between Internet addiction and aggression has been addressed. Ko et al 13 reported that although Internet use may reduce distress by providing immediate rewards and opportunities to engage in different activities, excessive use of the Internet is an important risk factor for aggression.…”
Section: Introductionmentioning
confidence: 99%